Exploitation of Legal Loopholes in the Regulatory System: A Justice and Legal Certainty Perspective - Basri Basri (PT. Anagata Sembagi Education, 2026)
Legal loopholes are a phenomenon inherent in every regulatory system, arising from editorial imperfections, normative voids, interpretive ambiguities, and social developments that outpace the formation of laws and regulations. This study aims to analyze the exploitation of legal loopholes from the perspective of substantive justice and legal certainty, by evaluating their impact on the integrity of the Indonesian legal system. Using normative legal research methods with statutory, conceptual, and case approaches, this study finds that opportunistic exploitation of legal loopholes creates tension between formal legality and substantive justice, and threatens public trust in the rule of law. The results indicate that legal loopholes stem from four main factors: (1) weaknesses in legislative drafting; (2) technological and economic developments that outpace regulations; (3) inconsistencies in judicial interpretation; and (4) conflicts of norms between regulatory levels. This study concludes that there is a need for a reconstruction of the legal formation paradigm that is oriented towards preventing regulatory loopholes from the planning stage, accompanied by strengthening judicial review mechanisms and developing the doctrine of teleological interpretation.